Analisis Faktor-Faktor yang Mempengaruhi Wali Murid dalam Memilih Sekolah Dasar antara Negeri dan Swasta - Lestari, Annisa Syukrina; Asih V.Y, Indhira; Rahmani , Anggi; Pribadi, Reksa Adya (Universitas Islam 45 Bekasi, 2025)
This study aims to analyze the factors that influence parents in choosing between public and private elementary schools in the Pamulang Barat Subdistrict, South Tangerang City. The selection of an elementary school is a complex process involving multidimensional considerations, both from the internal aspects of the family and the external characteristics of the schools. This research adopts a descriptive qualitative approach, with data collected through in-depth interviews with eight parent respondents and direct observation of school facilities. The results show that parents’ educational background and socioeconomic conditions significantly influence school choice. In addition, factors such as school facilities, flagship programs, and the quality of teaching staff are key considerations. Family values, social environment, school location, safety, access to information, and internal school policies also play integral roles in the decision-making process. These findings indicate that parents’ choice of elementary school is the result of an integration between rationality, emotion, and the social values upheld by the family.